Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1262/jrd.10-015t
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Fertility of Ewes after Intrauterine Insemination with Frozen-Thawed Semen During the Non-Breeding Season

Abstract: In this study, two successive field trials were conducted during the non-breeding season to investigate various factors affecting on fertility of Suffolk ewes after intrauterine insemination with frozen-thawed semen. In the first year (Experiment 1), three sperm numbers per insemination dose (0.25, 0.5 and 1 million sperm) and five sheep farms were used, and in the second year (Experiment 2), parity, age, body weight, body condition score (BCS) and postpartum days were investigated to compare pregnancy and lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
13
13
1
Order By: Relevance
“…However, the pregnancy rate was nonsignificantly higher after LAPAI (75.0 vs. 60.0%) than after TCAI with cervical relaxation treatment. LAPAI bypasses the cervix and deposits semen directly into uterine horn (Fukui et al, 2010). These findings conform to the study of Hiwas et al…”
Section: Effects Of Methods Of Ai On Pregnancy Rate In Indigenous Ewesupporting
confidence: 91%
“…However, the pregnancy rate was nonsignificantly higher after LAPAI (75.0 vs. 60.0%) than after TCAI with cervical relaxation treatment. LAPAI bypasses the cervix and deposits semen directly into uterine horn (Fukui et al, 2010). These findings conform to the study of Hiwas et al…”
Section: Effects Of Methods Of Ai On Pregnancy Rate In Indigenous Ewesupporting
confidence: 91%
“…In this sense, in highly prolific ewes like D'Man breed, higher levels of nutrition prior to and during mating were associated with improved reproductive performance, but in low prolific breeds such as Queue Fine de l'Ouest, neither ovulation rate nor lambing rate were affected by the dietary treatment. In a recent work by Fukui et al (2010) body weight did not significantly affect fertility. Body condition score (BCS) has proved useful as a management tool for subjectively assessing the nutritional status of ewes.…”
Section: Body Weight and Body Condition Scorementioning
confidence: 76%
“…With the aim of improving its efficiency, this paper focuses on identifying the main management effects affecting AI results when this technology is applied. Paulenz et al (2007), observed that the age of the ewes had a significant effect on the nonreturn rate, but not on lambing rate, whereas in Fukui et al (2010), both the pregnancy and lambing rates in the ewes significantly declined as age increased. The detrimental effect of increased fertility age could be explained by the fact that aged ewes have increased risks of reproductive disorders and decreased ovulation rates with quality ovulated oocytes compared with younger ewes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The inability to manipulate the ewe cervix per rectum, in the same way as in the cow, is a further difficulty. Thus, the application of MOET programmes, and indeed the use of frozen-thawed semen, which requires deposition within the uterus for successful fertilisation, still relies on laparoscopic penetration of the abdomen in ewes (Cognie, 1999;Cognie et al, 2003;Menchaca et al, 2009;Fukui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%